Kajian Sosiolinguistik Bahasa Indonesia Bidang Teknik di Institut Teknologi PLN Jakarta - Jumiati Jumiati; Yuliansyah Yuliansyah; Tri Astuti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Many students study in Jakarta but seem to learn nothing. In fact, most of them cannot speak good and correct Indonesian, in fact, there are also students who have not mastered Indonesian vocabulary. The phenomenon of learning difficulties occurs because of serious problems in education in Indonesia, one of which is the lack of mastery of Indonesian in universities. This study aims to reveal the existence of sociolinguistics on the attitudes/opinions of ITPLN students in using language in the campus environment. Finding sociolinguistic factors that strengthen and weaken the use of Indonesian in the engineering field. This study uses quantitative methods and correlational descriptive surveys, namely research conducted to obtain information about data, then processed with statistics with the preliminary study stage carried out with a quantitative descriptive approach. The results of this study show the value of the determinant coefficient (R2) = 0.192, which means that around 19.2% of changes in sociolinguistic variables and learning achievement can be explained by student learning achievement. Then based on the results of the t-test, sig0.000 <0.005 was obtained, meaning that the influence was significant. In other words, sociolinguistic variables provide a significant positive contribution to the learning achievement of ITPLN students. The results of the F test obtained F count 14.04 sig0.000<0.005 Ftable shows that Ha is accepted and Ho is rejected, meaning that there is a positive and significant influence. So it can also be concluded that the proposed hypothesis can be accepted.